Pro exchange Server 2013 Administration - Wesselius, Jaap (Apress, 2014)
Pro Exchange Server 2013 Administration is your best-in-class companion for gaining a deep, thorough understanding of Microsoft's powerful enterprise collaboration and communications server. Author Jaap Wesselius is at your side as you administer every facet of Exchange Server 2013, revealing tips, tricks, and little known facts that will make your administration life simpler and more effective. Along with revealing what's new in Exchange Server 2013, this well-paced, deeply engaging tutorial provides detailed deployment guidance, for upgraders and migrators as well as for organizations entirely new to the Exchange platform. The book details how all of the major Exchange components fit together, from SMTP messages to all kinds of clients. It also provides in-depth configuration examples with an eye toward creating scalable, reliable, and secure installations. Additionally, this guide covers the tools and techniques for monitoring an Exchange environment and troubleshooting when things go wrong. With Pro Exchange Server 2013 Administration, you will: • Learn how to install Exchange Server fresh or upgrade from a previous version • Get a comprehensive understanding of Exchange, with thorough coverage of Mailbox server and Client Access server • Understand the tools and techniques for configuring and managing your Exchange deployment to ensure scalability, reliability, efficiency and security • Learn how to monitor your deployment and prepare for any problems and how to troubleshoot any problems that do arise